1961
DOI: 10.1111/j.1365-2621.1961.tb00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of Almond Preference on Consumer Category and Type of Experimenta

Abstract: SUMMARY Three almond selections with distinct tastes and other characteristics were compared by male and female tasters in different types of experiments. The tasters differed in preferences and in distributions of recorded degrees of liking. Interactions between sex, almond selection, and type of experiment were present and important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1963
1963
1972
1972

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…The difference in preferences was surprisingly small when examined in this manner. As pointed out by Mrak et al (1959) and Baker et al (1961), some consumers are very sensitive to differences and others are very insensitive.. This ham study showed that some 45% could not detect differences due to sugar or its absence and were quite insensitive to this treatment.…”
Section: Resultsmentioning
confidence: 49%
“…The difference in preferences was surprisingly small when examined in this manner. As pointed out by Mrak et al (1959) and Baker et al (1961), some consumers are very sensitive to differences and others are very insensitive.. This ham study showed that some 45% could not detect differences due to sugar or its absence and were quite insensitive to this treatment.…”
Section: Resultsmentioning
confidence: 49%